Psychological Factors in Students' Attitudes towards the Digital Educational Environment (Case of Russian and Belarusian Universities) - Nataly P. Radchikova; Maria A. Odintsova; Marina G. Sorokova; Nina V. Kozyreva; Alexander P. Lobanov (National Research Mordova State University, 2023)
Introduction. The common educational space of Russia and Belarus is a condition for deepening integration processes underpinned by common historical roots, long experience of common development, goals and principles of cooperation. However, many aspects, including the prerequisites and factors of studentsʼ acceptance of digital technologies in higher education, are not sufficiently studied. The aim of the article is to present the results of research into the psychological factors of digital educational environment acceptance by students of Russian and Belarusian universities. Materials and Methods. The study involved 1 582 students from universities in Russia and Belarus aged 21,3 ± 6,3 years. To identify personality traits, Big Five Inventory-2 was used. The resources of self-regulation were determined using Personal Self-Activation Inventory and Self-Regulation Style Questionnaire. To determine the attitude to learning in the digital educational environment, AUDEE Scale was used, and to determine the attitude to learning activities - Activity-Related Experiences Assessment Technique. Results. The most important factors of digital educational environment acceptance for both samplings (Russia and Belarus) are not personality traits but activity-related experiences: the experience of pleasure in the absence of experiences of effort and void leads to acceptance of the digital educational environment. Modeling of significant conditions for achieving goals, evaluation of results and programming of actions, and insistency for the Belarusian sampling were also noted as important elements of digital educational environment acceptance. Therefore, the main factors are not the personality traits of the student, but the experiences that s/he experiences during the learning activity and some structural components of self-regulation. Similarity in models' quality and structure for two different countries supports the reliability of the results and serves a basis for practical recommendations for digital educational environment development and preparing students for work in it. Discussion and Conclusions. The conclusions made by the authors contribute to the problem of studentsʼ attitude to the university's digital educational environment. The materials of the article can be useful for university administration and teaching staff to improve both the university's digital educational environment and the methods of teaching using digital educational environment.